Epigenetic Regulations of Microglia/Macrophage Polarization in Ischemic Stroke - Qiu, Meiqian; Xu, En; Zhan, Lixuan (Frontiers in Molecular Neuroscience, 2021)
Ischemic stroke is one of the leading causes of death and disability worldwide. Microglia/macrophages (MMs)-mediated neuroinflammation contributes significantly to the pathological process of ischemic brain injury. Microglia, serving as resident innate immune cells in the central nervous system, undergo pro-inflammatory phenotype or anti-inflammatory phenotype in response to the microenvironmental changes after cerebral ischemia. Emerging evidence suggests that epigenetics modifications, reversible modifications of the phenotype without changing the DNA sequence, could play a pivotal role in regulation of MM polarization. However, the knowledge of the mechanism of epigenetic regulations of MM polarization after cerebral ischemia is still limited. In this review, we present the recent advances in the mechanisms of epigenetics involved in regulating MM polarization, including histone modification, non-coding RNA, and DNA methylation. In addition, we discuss the potential of epigenetic-mediated MM polarization as diagnostic and therapeutic targets for ischemic stroke. It is valuable to identify the underlying mechanisms between epigenetics and MM polarization, which may provide a promising treatment strategy for neuronal damage after cerebral ischemia.